2011
DOI: 10.1038/modpathol.2011.111
|View full text |Cite
|
Sign up to set email alerts
|

Increased gene copy number of ERG on chromosome 21 but not TMPRSS2–ERG fusion predicts outcome in prostatic adenocarcinomas

Abstract: The role of TMPRSS2–ERG gene fusion in prostate cancer prognostication remains controversial. We evaluated the prognostic role of TMPRSS2–ERG fusion using fluorescence in situ hybridization analysis in a case–control study nested in The Johns Hopkins retropubic radical prostatectomy cohort. In all, 10 tissue microarrays containing paired tumors and normal tissues obtained from 172 cases (recurrence) and 172 controls (non-recurrence) matched on pathological grade, stage, race/ethnicity, and age at the time of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 40 publications
2
51
0
Order By: Relevance
“…89 Although the TMPRSS2-ERG fusion gene is highly relevant in androgen-dependent prostate cancer, it has been shown to be bypassed in late stage castrationresistant prostate cancer in which oncogenic ERG is overexpressed through other mechanisms independent of TMPRESS2. 91 From the above discussion it is obvious that there is evidence for and against either model. However, genetic/ epigenetic aberrations previously thought to be exclusively or predominantly associated with advanced prostate cancer are now increasingly detected in early and premalignant disease because of the increasing sophistication and sensitivity of current assay techniques.…”
Section: Tmprss2-ergmentioning
confidence: 99%
“…89 Although the TMPRSS2-ERG fusion gene is highly relevant in androgen-dependent prostate cancer, it has been shown to be bypassed in late stage castrationresistant prostate cancer in which oncogenic ERG is overexpressed through other mechanisms independent of TMPRESS2. 91 From the above discussion it is obvious that there is evidence for and against either model. However, genetic/ epigenetic aberrations previously thought to be exclusively or predominantly associated with advanced prostate cancer are now increasingly detected in early and premalignant disease because of the increasing sophistication and sensitivity of current assay techniques.…”
Section: Tmprss2-ergmentioning
confidence: 99%
“…It has been known for more than 15 years as proto-oncogene with mitogenic and transforming activity [19,20]. [22], and an increased gene copy number of wildtype ERG has recently shown to be prognostic for PCa recurrence [23]. We detected over-expression of ERG mRNA and protein in the majority of analyzed PCa cases, while miR-145 exhibited an inverse regulation pattern.…”
Section: Discussionmentioning
confidence: 63%
“…Since 2005, when Tomlins 6 first described the presence of this fusion in PCa, a large number of studies have been published in this field. Some authors found a correlation between the presence of fusion and poor prognosis 36,44,[69][70][71] , but others found a correlation between the presence of fusion and good prognosis [72][73][74] or no correlation 31,[75][76][77][78] . The prognostic value of TMPRSS2-ERG rearrangements in selected studies is summarized in Table 1.…”
Section: Tmprss2-erg Gene Fusion As a Prognostic Markermentioning
confidence: 97%
“…Prognostic value of TMPRSS2-ERG rearrangements in selected studies. 78 . They reported that TMPRSS2-ERG gene fusion was not associated with PCa recurrence, supporting the lack of prognostic significance of the ERG gene fusion determined by FISH.…”
Section: Tmprss2-erg Gene Fusion As a Prognostic Markermentioning
confidence: 99%